2015
DOI: 10.1039/c5dt02445e
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric and spectroscopic studies on the copper(ii) complexes of rat amylin fragments. The anchoring ability of specific non-coordinating side chains

Abstract: Copper(II) complexes of peptides modelling the sequence of the 17-22 residues of rat amylin have been studied by potentiometric, UV-Vis, CD and ESR spectroscopic methods. The peptides were synthesized in N-terminally free forms, NH 2 -VRSSNN-NH 2 , NH 2 -VRSSAA-NH 2, NH 2 -VRAANN-NH 2 , NH 2 -VRSS-NH 2 , NH 2 -SSNN-NH 2 , NH 2 -SSNA-NH 2 and NH 2 -AANN-NH 2 , providing a possibility for the comparison of the metal binding abilities of the amino terminus and the -SSNN-domain. The amino terminus was the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Critically, it has been established that insulin resistance and diabetes lead to increases in oxidative stress directly [6265] or indirectly through increasing inflammation [66, 67]. Incidentally, PRAM administration in T2DM patients reduces the levels of serum markers of oxidative stress [43, 44] and can also form a complex with Cu (II) [68] that can mimics antioxidant enzymes to reduce ROS [69, 70]. Importantly, previous work has shown the ability of PRAM to reduce lipid peroxidation damage and inflammatory markers and stress related responses HO-1 in a mouse model of accelerated aging [29].…”
Section: Discussionmentioning
confidence: 99%
“…Critically, it has been established that insulin resistance and diabetes lead to increases in oxidative stress directly [6265] or indirectly through increasing inflammation [66, 67]. Incidentally, PRAM administration in T2DM patients reduces the levels of serum markers of oxidative stress [43, 44] and can also form a complex with Cu (II) [68] that can mimics antioxidant enzymes to reduce ROS [69, 70]. Importantly, previous work has shown the ability of PRAM to reduce lipid peroxidation damage and inflammatory markers and stress related responses HO-1 in a mouse model of accelerated aging [29].…”
Section: Discussionmentioning
confidence: 99%
“…If the N-terminal amino group is available for binding, it serves as an anchoring site for Cu 2+ . However, even if this group is acetylated, the - 19 SSNN 22 - sequence can still form stable complexes with Cu 2+ , where the amide nitrogens are the binding sites, and the asparagine side chains additionally stabilize the square planar Cu 2+ complex. , …”
Section: Introductionmentioning
confidence: 99%
“…30 However, even if this group is acetylated, the -19 SSNN 22 -sequence can still form stable complexes with Cu 2+ , where the amide nitrogens are the binding sites, and the asparagine side chains additionally stabilize the square planar Cu 2+ complex. 29,31 Sanchez-Lopez et al showed that in several amylin fragments, Cu 2+ binds to the imidazole N1 of His18 and to the deprotonated amides of Ser19 and Ser20, which is, from a thermodynamical point of view, not the most common type of coordination. In such cases, a seven-membered chelate ring is formed instead of the thermodynamically preferred sixmembered ring that would have formed if the amides in the N-terminal direction had participated in binding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The interactions of Cu 2+ with the rat fragments of amylin were also extensively studied, showing the formation of a square planar complex, in which copper(II) is bound to four amide nitrogens. 41 Knowing the importance of the impact of copper and zinc on the aggregation and membrane disrupting abilities of amylin, this work tries to understand the interactions between Cu 2+ and Zn 2+ with the membrane disrupting fragment of human amylin, KC̲ NTATC̲ ATQRLANFLVHS-NH 2 (amylin 1-19 ), focusing on the thermodynamics of such complex formation and precisely pointing out metal binding sites. The work provides a detailed understanding of the coordination chemistry of amylin-metal interactions and gives insight into bioinorganic chemistry of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%